A Case of Pseudohyponatremia in the Setting of Pegaspargase-Induced Hypertriglyceridemia in an Adult T-Cell Lymphoblastic Leukemia Patient - Asim Ahmad; Matthew Joseph (Case Reports in Hematology)
We present a rare case of pseudohyponatremia in a 20-year-old male patient with adult T-cell acute lymphoblastic leukemia (ATLL). The patient was admitted for a mediastinal mass with superior vena cava syndrome and was receiving pegaspargase therapy. The pseudohyponatremia was found to be secondary to hypertriglyceridemia associated with the pegaspargase treatment. In this case report, we discuss the important considerations in the management of adult ATLL patients receiving pegaspargase therapy, and the specific approaches taken to care for the patient described in this case.